Tipologia regimului de guvernare [Articol] - Cârnaț, Teodor; Popa, Cristina (My University, 2017)
The article deals with the identification of definitory features of governing regime and analysis all its types. This, in the doctrine there are presented the following types of governing regime, in dependence of distribution of power functions between political institutions and on before who the executive is politically responsible: presidential regime, parliamentary regime, semipresidential regime and semiparliamentary regime.
Keywords: governing regime; democracy; presidential; parliamentary; semi-presidential; semi-parliamentary